2014
DOI: 10.1186/s40527-014-0001-9
|View full text |Cite
|
Sign up to set email alerts
|

Internal control, related party transactions and corporate value of enterprises directly controlled by Chinese central government

Abstract: State-owned enterprises (SOEs) play a crucial role in China's economy. Those directly controlled by the central government (CSOEs) take leading positions almost in all industries in China. In this paper, we analyse the impacts of internal control quality of CSOEs on related party transactions and corporate value of CSOEs after the Chinese government introduced regulatory changes and the split share structure reform. Current literature offers little empirical evidence in this area. The primary information colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Therefore, it has been more than 90 years since management control was discussed as an independent fi eld in theory. The theoretical framework has been established and improved including the nature of management control, the elements of management control, the procedures of management control and the modes of management control, etc., which provides an integrated theoretical and methodology system for management control (Zhang Xianzhi 2004, 2014. As for management control research in Britain, there is a specialized Management Control Association which studies a series of special topics on management control and has developed many collected papers including all aspects of management control.…”
Section: The Development Of the Theoretical And Methodology System Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it has been more than 90 years since management control was discussed as an independent fi eld in theory. The theoretical framework has been established and improved including the nature of management control, the elements of management control, the procedures of management control and the modes of management control, etc., which provides an integrated theoretical and methodology system for management control (Zhang Xianzhi 2004, 2014. As for management control research in Britain, there is a specialized Management Control Association which studies a series of special topics on management control and has developed many collected papers including all aspects of management control.…”
Section: The Development Of the Theoretical And Methodology System Ofmentioning
confidence: 99%
“…According to this regulation, companies in the initial public offering (IPO) process must have a sound and effective internal control system that should guarantee the reliability of fi nancial reports, compliance with laws and regulations, effi ciency and effectiveness of business operations (Tong et al 2014 ). During the last decade, internal control systems have been established in most listed companies and some unlisted companies.…”
Section: The Establishment and Implementation Of Standards For Enterpmentioning
confidence: 99%
“…Li, Sun, and Wang (2004) state that efficient internal control can, to some extent, prevent the company's controlling behavior from committing fraudulent actions as a result of agency problems, such as related transactions, manager's opportunistic behavior, and earnings management. The main function of the internal auditor is to ensure and assist management regarding the supervisory function, improve management effectiveness and implement governance within the company to increase value and improve company performance (Tong et al, 2014). Based on the research findings above, in this study the formulation of the hypothesis can be presented as follows: H3: Internal auditors have a negative effect on the tunneling of RPT loans.…”
Section: Introductionmentioning
confidence: 93%
“…The Internal Audit Charter contains, among other things, the structure and position, responsibilities and authorities, code of ethics, and policies for the internal audit function. Tong, Mingzhu, and Feng (2014) conducted a study on BUMN in China that found that the quality of internal auditors plays an important role in controlling related transactions by controlling shareholders that have the potential to harm the interests of minority shareholders. Li, Sun, and Wang (2004) state that efficient internal control can, to some extent, prevent the company's controlling behavior from committing fraudulent actions as a result of agency problems, such as related transactions, manager's opportunistic behavior, and earnings management.…”
Section: Introductionmentioning
confidence: 99%
“…Internal control is commonly regarded as a key deterrent of fraud [15]. The effectiveness of internal control is always evaluated to ensure there is no hole or weakness that can emerge fraud behavior [16]. Internal control should be suitable and compliance with regulations and policies to combat fraud.…”
Section: Internal Control and Internal Auditmentioning
confidence: 99%